(untitled) (Bangladesh Journal of Botany, 2021)
The present experiment was conducted in order to prepare a suitable substrate composition using wheat straw and also to ascertain the effect of various levels of nitrogen supplementation on the yield and biological efficiency of Pleurotus mushroom. The strain DMRP-205 of Pleurotus djamor was used in the study. Among different treatment combinations, maximum biological efficiency of 75.11% was recorded in T2 with 0.5% of urea supplementation. It was also observed that, though the higher nitrogen supplementation does not increase the yield proportionately, it has significant effect on the spawn run period, cropping duration and colour intensity of the basidiocarp. The study necessitates the nitrogen supplementation at optimum levels (0.5%) to realize the maximum yield in P. djamor cultivation. Bangladesh J. Bot. 50(2): 227-233, 2021 (June)